1997
DOI: 10.1116/1.580647
|View full text |Cite
|
Sign up to set email alerts
|

Surface studies of model supported catalysts: NO adsorption on Rh/CeO2(001)

Abstract: The adsorption and reaction of NO on a model catalyst composed of Rh supported on ceria has been studied. CeO2 films were grown epitaxially by laser ablation onto SrTiO3(001) substrates. X-ray diffraction and transmission electron microscopy indicate the films are single crystalline with (001) orientation. Comparison of experimental and computer simulated ion scattering distributions indicate that an annealed CeO2 surface is well ordered and is composed of both O and Ce terminated domains. Exposures to CO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…After cleaning, the impurity level was below the experimental detection limit, the surface was fully oxidized, and there was no evidence of a breakthrough of Sr or Ti. Surface structural characterization was not conducted on these samples; however, low‐energy electron diffraction patterns and angle‐dependent low‐energy ion scattering from films grown in the same manner indicated that the surface was crystalline and reasonably well ordered …”
Section: Methodsmentioning
confidence: 94%
“…After cleaning, the impurity level was below the experimental detection limit, the surface was fully oxidized, and there was no evidence of a breakthrough of Sr or Ti. Surface structural characterization was not conducted on these samples; however, low‐energy electron diffraction patterns and angle‐dependent low‐energy ion scattering from films grown in the same manner indicated that the surface was crystalline and reasonably well ordered …”
Section: Methodsmentioning
confidence: 94%
“…6,7,37 As the lattice parameters are a film = 0.5411 nm and a sub = 0.3905 nm, the lattice mismatch exhibited due to this orientation relationship is ∼2%. This lattice mismatch implies that the equilibrium misfit dislocation spacing to relieve long-range coherency stresses is 18.5 nm, which is calculated using d dis = |b|a sub /(a film − a sub ), where b is the Burgers vector component parallel to the interface, and in this case assumed to be a film 110 .…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with experimental results for the CeO 2 /STO interface, where O terminated planes are observed, 7, 54 although Ce and O terminated planes in equal ratio have also been observed. 6 More importantly, to eliminate the surface dipole that arises by terminating the ideal fluorite crystal in a (100) direction, half of the oxygen ions have been moved from one surface of CeO 2 to the other, similar to the lowest energy (100) surface found for UO 2 , resulting in sub-stoichiometric surfaces that are dipole-free. 55 The stepped interface model shown in Figure 1(c) was found to be structurally stable upon annealing at 2000 K for 10 ps.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations